Endometrial Thickness- a Practical Prospective Marker for the Risk of Surgical Intervention after RU486 Induced Abortion - Zeev Blumenfeld M.D; William Abdallah; Dalia Kaplan; Ori Nevo (SAGE Publishing, 2008)
Background Medical termination of pregnancy [TOP] during the early first trimester is commonly used. However, treatment failure which warrants surgical intervention occurs in small proportion of patients. Our objective was to examine the effectiveness and predictive value of sonographic measurement of endometrial thickness during a follow up visit after medical abortion as an accurate predictor of the necessity of curettage for completion of pregnancy termination. Methods Women who opted for medical TOP where treated by single dose of RU486 followed by a single dose of misoprostol. Endometrial thickness was evaluated by transvaginal U.S. at 14 days after misoprostol tretament. The data was collected prospectively for this cohort study which includes all the women undergoing medical abortion in the first seven weeks of gestation. Results In 34.7% of the patients the endometrial width was > 11 mm on the follow-up visit. Surgical intervention was performed in 18% of these patients, for a failure rate of the medical termination of pregnancy [TOP] of 6.25%, as compared with no failure rate in those with endometrium < 11 mm, P < 0.001. In the patients where the endometrium was 11-12 mm on follow-up, the failure rate was 5%, and if > 12 mm the failure was 5.9%. In cases where the endometrium was 12-13 mm the failure rate was 27.3%, and if >13 mm the failure was 18.9%. When the endometrium was 13-14 mm the failure rate was 10%, and when >14 mm the failure was 23.7%. Half of the 18 patients who had undergone dilatation and curettage [D&C] for completion of the TOP, had endometrium > 14 mm, one to two weeks after the medical abortion. Conclusion Measurement of endometrial width after medical TOP is beneficial in segregating patient to low or high risk for surgical treatment of retained product of conception [POC]. Using a cutoff of 11 mm during the follow-up visit after medical TOP, 18% of the patients may need dilatation and curettage to complete the pregnancy termination, and if it is >14 mm, half of them may need surgical intervention. There is no difference between 11 and 14 mm regarding the risk of surgical intervention after medical TOP.